Faktor yang Memengaruhi Purchase Intention melalui Brand Image pada Skincare Lokal di Kota Batam - Ohanna, Nida; Kesumahati, Erilia (Jurnal Manajerial, 2024)
Background – During the COVID-19 epidemic, increased consumer interest in skincare is generating commercial potential for local skincare products in Batam City. Attractive and trustworthy brand ambassadors play an important role in influencing consumers' purchase intentions for products by enhancing brand image and increasing awareness of product quality, which will ultimately motivate purchases. Aim – The purpose of this study is to analyze the relationship between various factors (attractiveness, expertise, trustworthiness of brand ambassadors, E-WOM, and social media marketing) on purchase intention of local skincare products in Batam City. Design / methodology / approach – The purposive sampling method was used to collect data from 386 individuals who have used local skincare products in Batam City. The questionnaire was distributed using Google Form in April 2023. Findings – The results of the Structural Equation Modeling - Partial Least Square (SEM-PLS) analysis show a positive and significant influence of attractiveness, expertise, trustworthiness, E-WOM, social media marketing variables on purchase intention through brand image. Conclusion - The brand image of skin care products will increase if you use a brand ambassador, where this brand ambassador has a strong influence in increasing the desire to buy skin care products. Research implication – These findings provide insight that social media marketing approaches are efficient, brand ambassadors are influential, and E-WOM is effective in improving brand image and purchase intention of local skincare customers. Limitations – The limitation of this study is that the brand image variable can only be explained by 46.5% by variables such as attractiveness, knowledge, trustworthiness, E-WOM, and social media marketing. Other variables not studied, such as respect and similarity, can explain the remaining 53.5%. Similarly, the purchase intention variable can only be explained by 39.6% by the factors considered, with the remaining 60.4% possibly influenced by other variables such as sales promotion and product quality.